Effect of mixed planting on soil nutrient availability and microbial diversity in the rhizosphere of Parashorea chinensis plantations - Li, Wannian; Xie, Le; Xu, Yuanyuan; Yang, Mei (Frontiers in Microbiology, 2024)
Parashorea chinensis (Pc) is an endangered tree species endemic to tropical and subtropical China. However the acidic red soil areas where it is distributed generally face nutrient limitation. The study of the effects of mixed planting on soil biogeochemical processes contributes to the sustainable management and conservation of Pc. We selected pure and mixed stands of Pc and collected its rhizosphere and bulk soil samples to clarify the effect of mixed planting on the soil microbial community and the nutrient status. The results showed that (1) All stands were strongly acidic phosphorus-deficient soils (pH < 4.0, available phosphorus < 10.0 mg•kg -1 ). There was a significant rhizosphere aggregation effect for soil organic C, total and available N and K, microbial biomass, and inorganic P fraction. (2) The mixed planting significantly increased the soil water content, organic C, available nutrients, the activities of β-1,4-glucosidase and urease, and microbial biomass. The inorganic P fractions are more influenced by rhizosphere, while organic P fractions are more influenced by tree species composition. (3) Fungi and their ecological functions are more susceptible to tree species than bacteria are, and have higher community compositional complexity and α -diversity in mixed plantations. And mixed planting can improve network complexity among key microorganisms. (4) The correlation between soil microorganisms and environmental factors was significantly higher in mixed forests than in pure forests. Soil organic C, available N and P, microbial biomass C and N, β-1,4-glucosidase, and stable P fractions were the key environmental factors driving changes in fungal and bacterial communities. In conclusion, the mixed planting patterns are more advantageous than pure plantations in improving soil physicochemical properties, enhancing nutrient effectiveness, and promoting microbial activities and diversity, especially Pc mixed with Eucalyptus grandis × E. urophylla is more conducive to soil improvement and sustainable management, which provides practical references for relocation protection of endangered tree species and species selection and soil fertility management in mixed planting. In addition, the study highlighted the key role of rhizosphere microenvironment in soil nutrient cycling and microbial community structure, which provides new perspectives for a deeper understanding of soil-microbe-plant interaction mechanisms.